Analisis Yuridis Fenomena Ujaran Kebencian Terhadap Etnis Keturunan Arab–Yaman di Indonesia dalam Perspektif Hukum Pidana dan Undang-Undang ITE - Rejja Pahrepi; Muhammad Fathinnuddin (PT Elaborium Elevasi Indonesia, 2026)
This study will discuss the phenomenon of racial and ethnic hate speech against people of Arab–Yemeni descent, in this case the Habib from the Bani Alawi or Ba’alawi family group. With the growing use of social media as a public space, criminal acts such as defamation, hate speech, fake news, slander, and acts of racial and ethnic discrimination have the potential to generate broader social implications within society. There is concern that this phenomenon will lead to the separation of groups in society based on ethnic, religious, and racial diversity. The purpose of this study is to analyze the legal basis and how the Criminal Law and Law No. 1 of 2024 concerning Electronic Information and Transactions are applied to the phenomenon of racial and ethnic hate speech. The phenomenon of hate speech against people of Arab–Yemeni or Habib descent is also related to human rights because it involves discrimination based on race and ethnicity, which then labels their identity negatively. This study uses a legal-normative approach by analyzing secondary data namely legislation and scientific literature. The results of this study will show that there are acts of hate speech against race and ethnicity targeting Arab–Yemeni descendants or Habib in Indonesia and their relationship with the ITE Law and the potential for human rights violations in the form of racial and ethnic discrimination